DLX3-Dependent STAT3 Signaling in Keratinocytes Regulates Skin Immune Homeostasis - Bhattacharya, Shreya; Kim, Jin-Chul; Ogawa, Youichi; Nakato, Gaku; Nagle, Veronica; Brooks, Stephen R.; Udey, Mark C.; Morasso, Maria I. (ELSEVIER SCIENCE INC, 2018)
Epidermal-specific deletion of the homeobox transcription regulator DLX3 disrupts keratinocyte differentiation and results in an IL-17-linked psoriasis-like skin inflammation. To identify the epidermal initiating signals produced by DLX3-null keratinocytes, we performed acute deletion of DLX3 in adult epidermis using a tamoxifen-inducible Krt14-cre/ERT system. K14CreERT;DLX3(fl/fl) skin exhibited dysregulated expression of differentiation-associated genes, upregulation of proinflammatory cytokines, and accumulation of Langerhans cells and macrophages within 3 days of tamoxifen-induced DLX3 ablation. We also observed increased accumulation of IL-17A-secreting V gamma 4 gamma delta T cells and heightened levels of IL-17 and IL-36 family of cytokines starting 1 week after DLX3 deletion. Interestingly, transcriptome profiling of K14CreERT;DLX3(fl/fl) epidermis at 3 days identified activated STAT3 as a transcriptional regulator and revealed differential expression of STAT3 signaling-related genes. Furthermore, activation of STAT3 was strongly increased in K14CreERT;DLX3(fl/fl) skin, and topical treatment with an inhibitor of STAT3 activation attenuated the immune phenotype. RNA-seq analysis of vehicle and STAT3 inhibitor treated K14CreERT;DLX3(fl/fl) skin identified differentially expressed genes associated with inhibition of leukocyte infiltration. Collectively, our results show that DLX3 is a critical regulator of STAT3 signaling network that maintains skin homeostasis.
Keywords: CORNIFIED ENVELOPE; LANGERHANS CELLS; T-CELLS; TRICHODENTOOSSEOUS SYNDROME; EPIDERMAL DIFFERENTIATION; SUSCEPTIBILITY LOCI; BARRIER FUNCTION; GENE-EXPRESSION; DEFICIENT MICE; HAIR FOLLICLE